Modified ternary positive electrode material as well as preparation method and application thereof

Through the preparation method of modified ternary positive electrode material, the two-pass cladding mechanism is used to reduce alkali content and improve dispersion, the problems of poor conductivity and poor cycle stability of nickel-cobalt-manganese ternary positive electrode material are solved, and better Comprehensive performance.

CN119447240AActive Publication Date: 2025-02-14HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411570457.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-14
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The nickel, cobalt, manganese ternary cathode material in lithium-ion batteries has problems such as excessive alkali content and uneven dispersion of elements, resulting in poor conductivity, poor cycle stability and poor comprehensive performance.

Method used

By using the preparation method of the modified ternary positive electrode material, a premixed solution is formed by mixing the acid ester solvent, the first additive and polyvinylidene fluoride, and then mixing it with the ternary positive electrode material and then first coated after drying and sintering. , and then mixed with the second additive and lubricant for ball milling for a second coat, and a two-coated coating mechanism is constructed to reduce alkali content and improve dispersion.

Benefits of technology

It effectively reduces the alkali content on the surface of the ternary positive electrode material, improves the partial dispersion of elements, and improves the conductive, cyclic stability and comprehensive performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447240A_ABST
    Figure CN119447240A_ABST
Patent Text Reader

Abstract

The invention provides a modified ternary positive electrode material and a preparation method and application thereof.The preparation method comprises the steps that a ternary positive electrode material and a premixed solution obtained by mixing an acid ester solvent, a first additive and polyvinylidene fluoride are mixed, and then a two-time coating layer mechanism is constructed in a sintering and ball-milling mode; the modified ternary positive electrode material is obtained. According to the preparation method, by constructing a two-time coating layer mechanism, on one hand, residual alkali on the surface of the ternary positive electrode material can fully react in the coating process, a coating layer is formed on the surface of the ternary positive electrode material in situ, and the residual alkali on the surface of the material is reduced; on the other hand, a high-temperature heat treatment mode and a ball milling mode are adopted in the two coating processes respectively, so that the surface structure of the material can be further stabilized, oxygen removal of the ternary material under high-voltage and high-temperature conditions is inhibited, and the electrochemical performance, the technological processing performance and the cycling stability of the ternary positive electrode material are improved; and the overall particle size distribution and the compaction density of the modified ternary positive electrode material can also be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a modified ternary positive electrode material and a preparation method and application thereof. Background Art

[0002] As the field of lithium-ion batteries continues to develop and progress, the market has further put forward higher demands on the performance of lithium-ion batteries, specifically on the performance of lithium-ion batteries in various aspects such as rate, cycle capacity retention rate, and energy density.

[0003] Lithium-ion batteries mainly include a positive electrode, a negative electrode and an electrolyte. The preparation of the positive electrode is usually carried out by the following method: the electrode active material, the binder and the conductive agent (such as conductive carbon, etc.) for improving the electronic conductivity are placed in a dispersion medium to make a slurry coating liquid, and then the coating liquid is evenly applied on the electrode collector by a coating device, and the positive electrode of the battery is obtained after the dispersion medium evaporates. Among them, the binder is usually polyvinylidene fluoride (PVDF), and the dispersion medium is usually a non-aqueous dispersion medium such as N-methyl-2-pyrrolidone (NMP). In the process of preparing the positive electrode of the battery, it is necessary to ensure the dispersibility and stability of the slurry coating liquid.

[0004] Nickel-cobalt-manganese ternary material is a commonly used electrode active material. It is considered to be one of the most promising battery positive electrode materials due to its high energy density and relatively low manufacturing cost. However, there are also some problems in the application of nickel-cobalt-manganese ternary materials, which seriously restricts its development, mainly including the following aspects: First, as the nickel content in nickel-cobalt-manganese ternary materials increases, the battery will have serious capacity decay problems during the cycle. This is because there will be unstable lithium residues (mainly Li2CO3 and LiOH) on the surface of nickel-cobalt-manganese ternary materials, which will cause capacity decay. On the other hand, the ionic radius of lithium ions and divalent nickel ions is similar, which will cause lithium-nickel mixed arrays in the battery. As the cycle progresses, the positive electrode material will transform into the rock salt phase, which is manifested as a significant increase in the direct current resistance (DCR) of the material. Under the combined effect of these two factors, the battery will eventually suffer from serious capacity decay problems. Second, nickel-cobalt-manganese ternary positive electrode materials will produce intergranular cracks during the cycle, and the electrolyte will erode the inside of the material along the cracks, resulting in a shortened cycle life of the material. Third, since the positive electrode of lithium-ion batteries now mostly uses polyvinylidene fluoride (PVDF) slurry, there is too high residual alkali content (especially LiOH, LiCO3). The alkaline group will attack the CF bond and CH bond in polyvinylidene fluoride (PVDF), so that a part of the polyvinylidene fluoride in the slurry will form carbon-carbon double bonds, which will increase the viscosity of the slurry and even form a gel state. The local or overall gel in the slurry will cause uneven composition of the positive electrode coating layer, affecting the performance when the positive electrode of the battery is prepared later. In addition, the material with too high alkali content will also react chemically with aluminum foil to generate Al(OH)3 insoluble substances. The flocculent precipitation will also have a certain hindering effect on the circulation of lithium ions in the battery. Furthermore, lithium hydroxide will react with lithium salts in the electrolyte to produce HF gas, which will cause corrosion of metal parts inside the battery, and at the same time will destroy the SEI film, consume active lithium in the system, and accelerate the attenuation of battery performance. Lithium carbonate reacts with HF to release CO2 gas, affecting the safety of battery use. Therefore, reducing the LiOH content on the surface of the ternary material is beneficial to improving the electrochemical performance and cycle performance of the battery and thus improving the overall performance of the battery.

[0005] In the process of preparing the positive electrode of the battery, the dispersion and stability of the coating liquid play an important role in the performance of the ternary electrode sheet, and are also of great significance to the effective performance of the overall performance of the battery cell. The dispersion problem in the process of slurrying of nickel-cobalt-manganese ternary materials is a key issue in the research of lithium batteries. The uneven dispersion of the coating liquid will affect the contact between the positive electrode active material and the binder and the conductive agent, and then affect the transmission of conductive electrons and lithium ions, reduce the conductivity and cycle performance of the ternary material, and reduce the compaction density of the electrode sheet. The mixing process of powdered substances is a kind of agglomeration process. According to the reasons for the formation of powder agglomeration, the agglomeration phenomenon of powders can be divided into soft agglomeration and hard agglomeration. The soft agglomeration of powders is formed by the combined action of electrostatic force and van der Waals force between powder particles, which is easier to disperse; while the hard agglomeration of powders is mainly formed by chemical bonds, so it is more difficult to disperse. Among them, the slurrying process of ternary materials is mostly a soft agglomeration process. Therefore, the dispersibility of the ternary material can be improved by surface modification of the powder of the ternary material. Organic molecules with good compatibility with the liquid solvent can be grafted onto the particle surface through chemical reaction to change the surface properties of the particles and achieve a stable dispersion effect.

[0006] In addition, the preparation process of the positive electrode slurry involves the dispersion of the positive electrode material powder, during which the positive electrode material is always in the process of high-speed stirring, ball milling or mutual collision. However, this process may damage the surface of the positive electrode material, exposing the new surface of the material to the slurry. On the one hand, it is easy to generate a large number of dangling bonds on the new interface to capture protons in the slurry; on the other hand, this process will make it easy for lithium ions to detach from the lithium layer, affecting the acidity and alkalinity of the slurry, and then causing the alkalinity of the slurry to increase, causing gelation. Therefore, how to improve the dispersibility and stability of the positive electrode material so that its structure is not easily destroyed during the preparation of the positive electrode slurry and improve the electrochemical performance of the material is a technical problem that needs to be solved urgently.

[0007] In summary, reducing the alkali content in the ternary positive electrode material and improving the internal dispersion of each element in the ternary positive electrode material are currently the key to improving the cyclability and stability of the ternary positive electrode material and improving the comprehensive performance of the ternary positive electrode material. Therefore, this application is specially proposed. Summary of the invention

[0008] The main purpose of the present invention is to provide a method for preparing a modified ternary positive electrode material to solve the problems of uneven internal dispersion of the elements in the material caused by excessively high alkali content in the ternary positive electrode material in the prior art, which in turn leads to poor conductivity and poor battery cycle stability when the ternary positive electrode material is used in batteries.

[0009] In order to solve the above problems, the present invention provides a method for preparing a modified ternary positive electrode material, which comprises the following steps: step (1), mixing an acid ester solvent, a first additive and polyvinylidene fluoride to obtain a premixed solution; the first additive is a salt of at least one of the metal elements Sn, Zn, Ti, Bi, Ta, Li and Zr; step (2), mixing the premixed solution and the ternary positive electrode material to obtain a mixed slurry; step (3), drying and sintering the mixed slurry to perform a first coating to obtain a mixed material; step (4), mixing the mixed material, a second additive and a lubricant, and then ball milling to perform a second coating to obtain a modified ternary positive electrode material; the second additive is a conductive polymer additive.

[0010] Furthermore, in terms of weight percentage, the first additive in the premixed solution is 5-20%, the polyvinylidene fluoride is 5-20%, and the remainder is an acid ester solvent; preferably, the weight ratio of the ternary positive electrode material to the premixed solution is (1-5):1.

[0011] Furthermore, the weight ratio of the mixed material to the second additive is 1:(0.01% to 1%); the amount of the lubricant added is 0.01% to 0.1% of the sum of the weight of the mixed material and the second additive.

[0012] Further, the acid ester solvent is one or more of tributyl citrate, triethyl citrate, tri-n-hexyl citrate, tri(2-ethyl)hexyl citrate, acetyl tributyl citrate, acetyl triethyl citrate, acetyl n-butyl citrate, acetyl tri(2-ethyl)hexyl citrate, triacetin and diethylene glycol ethyl ether acetate; preferably, the first additive is one or more of zinc stannate, bismuth titanate, lithium tantalate, barium titanate, zirconate titanate; preferably, the second additive is polythiophene and / or sulfonated lignin; preferably, the lubricant is lithium stearate and / or zinc stearate.

[0013] Furthermore, the mixing process in step (2) includes: subjecting the premixed solution and the ternary cathode material to ultrasonic treatment, and then aging, and introducing a plasma-activated gas during the ultrasonic and aging process; preferably, the plasma-activated gas is an inert gas containing 5 to 20% carbon dioxide, and preferably the inert gas is at least one of argon and helium; preferably, the amount of the plasma-activated gas introduced is 20 to 100 mL / min; preferably, the power density of the plasma-activated gas is 0.01 to 5 W / cm 2 ; Preferably, the ultrasonic time is 0.5 to 5 hours; Preferably, the aging time is 1 to 12 hours.

[0014] Furthermore, the molecular formula of the ternary cathode material is LiNi x Co y M 1-x-yO2, wherein 0.5≤x<1, 0<y≤0.1, and (x+y)<1, and M is Mn and / or Al.

[0015] Furthermore, in step (3), sintering is carried out in a compressed air atmosphere with a humidity of 40 to 70%; preferably, the sintering temperature is 700 to 900°C; preferably, the sintering time is 2 to 8 hours; preferably, drying is carried out under nitrogen circulation conditions, the drying temperature is 100 to 200°C, and the drying time is 5 to 25 hours.

[0016] Furthermore, grinding balls are added to the mixture of the mixed material, the second additive and the lubricant during ball milling; preferably, the weight ratio of the grinding balls to the mixture consisting of the mixed material, the second additive and the lubricant is 1:(1-5); preferably, the ball milling time is 4-12h; preferably, the particle size of the ternary positive electrode material after ball milling is 2.5≤D50≤4μm.

[0017] According to another aspect of the present invention, there is also provided a modified ternary positive electrode material, which is prepared according to the above preparation method.

[0018] According to the third aspect of the present invention, there is also provided a lithium-ion battery, comprising a battery positive electrode prepared from the above-mentioned modified ternary positive electrode material.

[0019] The present invention provides a modified ternary positive electrode material and a preparation method and application thereof. The preparation method first mixes the ternary positive electrode material with a premixed solution obtained by mixing an acid ester solvent, a first additive and polyvinylidene fluoride, and then constructs a two-layer coating mechanism by sintering and ball milling to obtain a modified ternary positive electrode material. In the preparation method, a two-layer coating mechanism is constructed. On the one hand, during the coating process, the residual alkali on the surface of the ternary positive electrode material can be fully reacted and a coating layer can be formed in situ on the surface of the ternary positive electrode material, further reducing the residual alkali on the surface of the material; on the other hand, the two coating processes of the modified ternary positive electrode material are respectively subjected to high-temperature heat treatment and ball milling, which can not only stabilize the surface structure of the material, inhibit the oxygen release of the ternary material under high voltage and high temperature conditions, improve the electrochemical performance, process processing performance and cycle stability of the ternary positive electrode material, but also improve the overall particle size distribution and compaction density of the modified ternary positive electrode material. The modified ternary positive electrode material prepared by the preparation method of the present invention has better conductivity and cycle stability during application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0021] Figure 1The modified ternary positive electrode material in Example 1 of the present invention is an SEM image before and after modification, wherein A is an SEM image of the ternary positive electrode material before modification, and B is an SEM image of the modified ternary positive electrode material;

[0022] Figure 2 The XRD diagram of the modified ternary cathode material before and after modification in Example 1 of the present invention;

[0023] Figure 3 This is a graph showing the change in slurry viscosity when preparing positive electrode sheets before and after the modification of the modified ternary positive electrode material in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0025] As described in the background technology section, the excessively high alkali content in the ternary positive electrode material is one of the important reasons that affect the comprehensive performance of the ternary positive electrode material. The excessively high alkali content in the ternary positive electrode material will not only cause the alkaline groups therein to attack the CF bonds and CH bonds in polyvinylidene fluoride (PVDF), resulting in an uneven distribution of the material system, but will also react chemically with the aluminum foil to generate Al(OH)3 insoluble substances, further affecting the dispersion of the system. In addition, the HF gas and CO2 gas produced by the alkaline groups reacting with the components in the electrolyte will also affect the safety performance and comprehensive performance of the battery system. Therefore, reducing the alkali content of the ternary positive electrode material and improving the internal dispersion of each element are the key to improving the comprehensive performance of the ternary positive electrode material.

[0026] In order to solve the above problems, the present invention provides a method for preparing a modified ternary positive electrode material, which comprises the following steps: step (1), mixing an acid ester solvent, a first additive and polyvinylidene fluoride (PVDF) to obtain a premixed solution; wherein the first additive is a salt of at least one of the metal elements Sn, Zn, Ti, Bi, Ta, Li and Zr; step (2), mixing the premixed solution and the ternary positive electrode material to obtain a mixed slurry; step (3), drying and sintering the mixed slurry to perform a first coating to obtain a mixed material; step (4), mixing the mixed material, a second additive and a lubricant, and then ball milling to perform a second coating to obtain a modified ternary positive electrode material; wherein the second additive is a conductive polymer additive.

[0027] In the preparation method of the modified ternary material described in the present invention, the salt additive containing the above-mentioned metal element and polyvinylidene fluoride are firstly mixed with an acid ester solvent to obtain a premixed solution for modifying the ternary positive electrode material; then the ternary positive electrode material to be modified and the prepared premixed solution are fully infiltrated and mixed to obtain a mixed slurry; then the above-mentioned mixed slurry is subjected to a first coating through operations such as drying and sintering to obtain a mixed material; finally, the mixed material is mixed with a second additive and a lubricant, and the second additive and the mixed material are doped and coated by ball milling to obtain a modified ternary positive electrode material.

[0028] In particular, when preparing the modified ternary positive electrode material, the present invention constructs a double coating mechanism, and during the coating process, the residual alkali on the surface of the ternary positive electrode material can be fully reacted and a coating layer can be formed in situ on the surface of the ternary positive electrode material, thereby further reducing the residual alkali on the surface of the material. Specifically, during the preparation process, the present invention first uses a premixed solution prepared with an acid ester solvent, a first additive and polyvinylidene fluoride for infiltration and mixing, and then performs the first coating by drying and sintering. When preparing a premixed solution for infiltrating the ternary positive electrode material, an acid ester solvent is used as one of the components of the premixed solution, so that the acid ester solvent can undergo a hydrolysis reaction during the drying, sintering and other processes to produce an acidic substance, thereby enabling the alkaline substance in the ternary positive electrode material to undergo a neutralization reaction with the generated acidic substance, thereby helping to reduce the content of alkaline substances in the ternary positive electrode material. PVDF, as an excellent electrode modifier, can improve the conductivity and structural stability of the ternary positive electrode material, which is beneficial to improving the cycle stability of the modified ternary positive electrode material during use. By adding salt additives containing the above-mentioned metal elements to the premixed solution, the good conductivity of the metal ions therein can be utilized to further improve the conductivity of the modified ternary positive electrode material. After the premixed solution composed of the above-mentioned three components and the ternary positive electrode material are fully infiltrated and mixed, they are dried and sintered to achieve full doping and coating of the above-mentioned components with the ternary positive electrode material. In this process, the alkali content in the ternary positive electrode material can be fully reduced and the conductivity and stability of the ternary positive electrode material can be improved. Furthermore, the present invention mixes the mixed material obtained after the first coating with the second additive and the lubricant, and performs a second coating through a ball milling process. The second additive is added during the second coating process. The second additive is a conductive polymer additive. The addition of the above-mentioned type of additive is beneficial to improving the conductivity of the ternary material, especially after the above-mentioned additive is added, when the prepared ternary positive electrode material is used to prepare a positive electrode plate of a battery, it can effectively help to improve the conductivity of the plate.

[0029] In addition, the present invention has different ways of constructing the two coating mechanisms when preparing the modified ternary positive electrode material. The first coating mechanism construction process is carried out in the form of high-temperature heat treatment, which can not only help reduce the alkali content in the ternary material, but also further stabilize the surface structure of the material, inhibit the oxygen release of the ternary material under high voltage and high temperature conditions, and improve the electrochemical performance, process processing performance and cycle stability of the ternary positive electrode material. The second coating mechanism construction process is carried out in the form of ball milling. On the one hand, the morphology of the single crystal particles is trimmed by mechanical ball milling, the roundness of the particles is improved, and the uniformity and dispersibility of the single crystal particles are improved; on the other hand, the organic conductive material can be in-situ coated on the surface of the single crystal material during mechanical ball milling, and the organic medium is added during the grinding process, which can also reduce the generation of fine powder during the grinding process, improve the overall particle size distribution of the material, improve the dispersion stability of the slurry, and improve the compaction density of the pole piece, which is beneficial to improving the electrochemical performance of the battery. The surface coating to form an elastic interface layer is also beneficial to improve the stress caused by the expansion and contraction of the lattice during the charge and discharge process of the material.

[0030] In summary, the preparation method of the present invention, through the construction of two coating processes, on the one hand, reduces the alkali content in the ternary positive electrode material, improves the internal dispersion of each element of the ternary positive electrode material, and is beneficial to improving the comprehensive performance of the ternary positive electrode material; on the other hand, the two coating processes improve the conductivity and cycle stability of the ternary positive electrode material during use, so that the modified ternary positive electrode material has excellent comprehensive performance.

[0031] In a preferred embodiment, by weight percentage, the first additive in the premix solution is 5-20%, the polyvinylidene fluoride is 5-20%, and the balance is an acid ester solvent; preferably, the weight ratio of the ternary positive electrode material to the premix solution is (1-5): 1. The content of the metal acid salt additive, the polyvinylidene fluoride content, and the acid ester solvent content in the premix solution will affect the improvement of the alkali content, the conductivity, and the cycle stability of the modified ternary positive electrode material. By controlling the content of each component in the premix solution within the above range and controlling the addition ratio of the ternary positive electrode material to the premix solution within the above range, the prepared modified ternary positive electrode material can have more excellent comprehensive performance.

[0032] In a preferred embodiment, the weight ratio of the mixed material and the second additive is controlled to be 1:(0.01% to 1%); the amount of lubricant added is 0.01% to 0.1% of the sum of the weight of the mixed material and the second additive. The second additive is a conductive polymer additive, which is the main component of the second coating layer. Controlling the second additive and the lubricant and the mixed material after the first coating within the above range can make the secondary coating have a better effect, which is beneficial to improve the comprehensive performance of the modified ternary positive electrode material.

[0033] By way of example but not limitation, the acid ester solvent is one or more of tributyl citrate, triethyl citrate, tri-n-hexyl citrate, tri(2-ethyl)hexyl citrate, acetyl tributyl citrate, acetyl triethyl citrate, acetyl n-butyl citrate, acetyl tri(2-ethyl)hexyl citrate, triacetin and diethylene glycol ethyl acetate. Acid ester solvents serve to reduce the alkali content in the material during the modification of the ternary cathode material, and the selection of the above-mentioned specific acid ester solvents has a better effect. Preferably, the first additive is one or more of zinc stannate, bismuth titanate, lithium tantalate, barium titanate and zirconate titanate; preferably, the second additive is polythiophene and / or sulfonated lignin. The first additive is one of the components in the first coating layer, which can improve the conductivity and cycle stability of the modified ternary cathode material. The second additive is a conductive polymer additive, which is the main component in the second coating layer. The selection of the above-mentioned specific types of additives has a better effect on improving the conductivity of the ternary material and the conductivity of the pole piece after compaction, which is conducive to improving the comprehensive performance of the modified ternary cathode material. Preferably, the lubricant is lithium stearate and / or zinc stearate.

[0034] In a preferred embodiment, the mixing process in step (2) includes: subjecting the premixed solution and the ternary cathode material to ultrasonic treatment first, then aging, and introducing plasma activated gas during the ultrasonic and aging process. Ultrasonic treatment and aging during the mixing of the ternary material and the prepared premixed solution can facilitate a more uniform mixing and contact between the premixed solution and the ternary cathode material. In the ultrasonic and aging process, the introduction of plasma activated gas can, on the one hand, improve the contact between the ternary cathode material and the premixed solution, enhance their bonding force, adhesion and dispersibility, make them more closely and more uniformly contacted, and also help to reduce the alkali content of the material surface; on the other hand, the energy in the plasma activated gas can make the modified ternary cathode material have better conductivity and cycle stability. Preferably, the plasma activated gas is an inert gas containing 5 to 20% carbon dioxide, preferably the inert gas is at least one of argon and helium; preferably, the amount of plasma activated gas introduced is 20 to 100 mL / min; preferably, the power density of the plasma activated gas is 0.01 to 5 W / cm 2 . Selecting the plasma activated gas with the above properties can make the performance of the modified ternary cathode material more excellent. Preferably, the ultrasonic time is 0.5 to 5 hours; preferably, the aging time is 1 to 12 hours. Controlling the ultrasonic time and aging time within the above range can make the modified ternary cathode material have a better effect.

[0035] In a preferred embodiment, the molecular formula of the ternary cathode material is LiNi x Co y M 1-x-yO2, wherein 0.5≤x<1, 0<y≤0.1, and (x+y)<1, and M is Mn and / or Al. The modified preparation method of the ternary positive electrode material of the present invention can reduce the alkali content in the ternary positive electrode material, improve the dispersibility between the various element components in the material, and improve the comprehensive performance of the ternary positive electrode material. In particular, the ternary positive electrode material having the above components and parameters is modified, and the comprehensive performance of the modified ternary positive electrode material is better.

[0036] In a preferred embodiment, the sintering in step (3) is carried out in a compressed air atmosphere with a humidity of 40 to 70%. Controlling the humidity of the sintering environment within the above range during sintering can make the alkaline substances in the ternary positive electrode material easily concentrated on the surface of the particles, which is more conducive to the neutralization reaction and thus helps to reduce the content of alkaline substances in the material. Preferably, the sintering temperature is 700 to 900°C; preferably, the sintering time is 2 to 8 hours; preferably, the drying is carried out under nitrogen circulation conditions, the drying temperature is 100 to 200°C, and the drying time is 5 to 25 hours. Controlling the drying and sintering conditions during the first carbon coating process within the above range can achieve better results when the modified ternary positive electrode material is coated for the first time.

[0037] In a preferred embodiment, grinding balls are added to the mixture of the mixed material, the second additive and the lubricant during ball milling; preferably, the weight ratio of the grinding balls to the mixture of the mixed material, the second additive and the lubricant is 1:(1-5). Adding grinding balls to the ball milling system during the ball milling process and controlling the amount of grinding balls added to be within the above range can make the particle size of the modified ternary positive electrode material more uniform. Preferably, the ball milling time is 4-12h. Further preferably, the particle size of the modified ternary positive electrode material after ball milling is 2.5≤D50≤4μm. Controlling the particle size of the modified ternary positive electrode material within the above range can make the modified ternary positive electrode material have better comprehensive performance.

[0038] According to the second aspect of the present invention, a modified ternary positive electrode material is provided, wherein the modified ternary positive electrode material is prepared by the above-mentioned preparation method, and the contents of LiOH and LiCO3 in the modified ternary positive electrode material obtained by the above-mentioned preparation method are significantly lower than those in the ternary positive electrode material before modification.

[0039] According to a third aspect of the present invention, a lithium-ion battery is provided, comprising a battery positive electrode prepared from the above-mentioned modified ternary positive electrode material.

[0040] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0041] Example 1

[0042] The premixed solution is obtained by mixing triethyl citrate, PVDF and bismuth titanate in a weight ratio of 75%:5%:20%, and then the premixed solution is mixed with the ternary positive electrode material. The mixing process includes stirring the mixed slurry under ultrasonic conditions for 1 hour, then standing it for 8 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.65 Co 0.07 Mn 0.28 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 1:1, the main component of the plasma activation gas is argon, which contains 10% volume of carbon dioxide, and the flow rate of the plasma activation gas is 50mL / min, and the power density is 0.05W / cm 2 .

[0043] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 120°C and the drying time was 5 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 45%, the sintering temperature was 780°C and the sintering time was 5 hours to obtain a first coated mixed material.

[0044] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 0.5%:1, the amount of lubricant lithium stearate added is 0.05% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.588μm is obtained.

[0045] The modified ternary cathode material prepared in this application was characterized, and the results are shown in the attached figure. Figure 1 : SEM images before and after modification, wherein A is the SEM image of the ternary positive electrode material before modification, and B is the SEM image of the ternary positive electrode material after modification; Figure 2 XRD diagrams of the ternary cathode materials before and after modification; Figure 3 This is a graph showing the viscosity change of the slurry used in preparing positive electrode sheets from ternary positive electrode materials before and after modification.

[0046] Depend on Figure 1 From the SEM image, it can be seen that the modified ternary cathode material prepared by the preparation method of the present invention has a further improved particle roundness compared to the ternary cathode material before modification, which can make the modified ternary cathode material have better specific surface area characteristics, better dispersibility and better compaction density. Figure 2From the XRD diagrams of the modified ternary cathode material and the ternary cathode material before and after modification, it can be seen that the modified ternary cathode material presents a single α-NaFeO2 type layered structure, belonging to the R3m space group. In addition, the (006) / (102) and (108) / (110) peaks are obviously split, further indicating that the material has a good layered structure; and from the XRD diagram, it can be seen that the peak shape of the modified ternary cathode material is sharp and there are no impurity peaks, indicating that it has a good crystal form. The ternary cathode materials before and after modification were used to prepare cathode pole sheets, and the viscosity of the slurry used in the preparation of the cathode pole sheets was tested. The results are as follows: Figure 3 As shown. Figure 3 It can be seen from the change graph of the slurry viscosity when preparing the positive electrode sheet before and after the modification that the slurry viscosity when using the modified ternary positive electrode material to prepare the positive electrode sheet will not change significantly for a long time, especially compared with the viscosity of the positive electrode slurry prepared from the ternary positive electrode material before the modification, which shows that the slurry prepared from the modified ternary positive electrode material has better stability and dispersibility. Therefore, the method for modifying the ternary positive electrode material described in the present invention can greatly improve the stability and dispersibility of the material.

[0047] Example 2

[0048] The premixed solution is obtained by mixing triethyl citrate, PVDF and barium titanate in a weight ratio of 60%:20%:20%, and then the premixed solution is mixed with the ternary positive electrode material. The mixing process includes stirring the mixed slurry under ultrasonic conditions for 1.5 hours, then standing it for 12 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.7 Co 0.1 Mn 0.2 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 5:1, the main component of the plasma activation gas is argon, which contains 20% volume of carbon dioxide, and the flow rate of the plasma activation gas is 20mL / min, and the power density is 0.01W / cm 2 .

[0049] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 100°C and the drying time was 10 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 70%, the sintering temperature was 900°C and the sintering time was 2 hours to obtain the first coated mixed material.

[0050] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 0.5%:1, the amount of lubricant lithium stearate added is 0.05% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.916 μm is obtained.

[0051] Example 3

[0052] The premixed solution is obtained by mixing triethyl citrate, PVDF and barium titanate in a weight ratio of 90%:5%:5%, and then the premixed solution is mixed with the ternary positive electrode material. The mixing process includes stirring the mixed slurry under ultrasonic conditions for 1.5 hours, then standing it for 2 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.8 Co 0.1 Mn 0.1 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 5:1, the main component of the plasma activation gas is argon, which contains 20% volume of carbon dioxide, and the flow rate of the plasma activation gas is 100mL / min, and the power density is 0.01W / cm 2 .

[0053] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 100°C and the drying time was 20 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 70%, the sintering temperature was 700°C, and the sintering time was 5 hours to obtain the first coated mixed material.

[0054] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 0.5%:1, the amount of lubricant lithium stearate added is 0.05% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.947 μm is obtained.

[0055] Example 4

[0056] The premixed solution is obtained by mixing tributyl citrate, PVDF and zinc stannate in a weight ratio of 75%:5%:20%, and then the premixed solution is mixed with the ternary positive electrode material. The mixing process includes stirring the mixed slurry under ultrasonic conditions for 0.5 hours, then standing it for 12 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.5 Co 0.1 Mn 0.4 The weight ratio of the added amount of O2 ternary cathode material to the premixed solution is 1:1. The main component of the plasma activation gas is argon, which contains 5% volume of carbon dioxide. The flow rate of the plasma activation gas is 100 mL / min, and the power density is 0.01 W / cm 2 .

[0057] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 100°C and the drying time was 25 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 40%, the sintering temperature was 700°C and the sintering time was 8 hours to obtain the first coated mixed material.

[0058] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 1:0.01%, the amount of the lubricant lithium stearate added is 0.01% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:5, and after ball milling for 12 hours, a modified ternary positive electrode material with a particle size D50 of 2.502 μm is obtained.

[0059] Example 5

[0060] The tri-n-hexyl citrate, PVDF and lithium tantalate are mixed in a weight ratio of 75%:20%:5% to obtain a premixed solution, and then the premixed solution is mixed with the ternary positive electrode material. The mixing process includes first stirring the mixed slurry under ultrasonic conditions for 5 hours, then letting it stand for 1 hour, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.9 Co 0.01 Al 0.09 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 5:1, the main component of the plasma activation gas is helium, which contains 20% volume of carbon dioxide, and the flow rate of the plasma activation gas is 20mL / min, and the power density is 5W / cm 2 .

[0061] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 200°C and the drying time was 5 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 70%, the sintering temperature was 900°C and the sintering time was 2 hours to obtain the first coated mixed material.

[0062] The mixed material after the first coating obtained above, the second additive sulfonated lignin and the lubricant zinc stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 1:1%, the amount of lubricant lithium stearate added is 0.1% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 4 hours, a modified ternary positive electrode material with a particle size D50 of 4.006 μm is obtained.

[0063] Example 6

[0064] The premixed solution is obtained by mixing tri(2-ethyl)hexyl citrate, PVDF and zirconate titanate in a weight ratio of 75%:5%:20%, and then the premixed solution is mixed with the ternary cathode material. The mixing process includes stirring the mixed slurry under ultrasonic conditions for 1 hour, then standing it for 8 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.65 Co 0.07 Mn 0.28 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 1:1, the main component of the plasma activation gas is argon, which contains 10% volume of carbon dioxide, and the flow rate of the plasma activation gas is 50mL / min, and the power density is 0.05W / cm 2 .

[0065] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 120°C and the drying time was 5 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 45%, the sintering temperature was 780°C and the sintering time was 5 hours to obtain a first coated mixed material.

[0066] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 0.5%:1, the amount of lubricant lithium stearate added is 0.05% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.567 μm is obtained.

[0067] Example 7

[0068] The premixed solution is obtained by mixing acetyl tributyl citrate, PVDF and bismuth titanate in a weight ratio of 75%:5%:20%, and then the premixed solution is mixed with the ternary positive electrode material. The mixing process includes stirring the mixed slurry under ultrasonic conditions for 1 hour, then standing it for 8 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.65 Co 0.07 Mn 0.28 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 1:1, the main component of the plasma activation gas is argon, which contains 10% volume of carbon dioxide, and the flow rate of the plasma activation gas is 50mL / min, and the power density is 0.05W / cm 2 .

[0069] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 120°C and the drying time was 5 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 45%, the sintering temperature was 780°C and the sintering time was 5 hours to obtain a first coated mixed material.

[0070] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 0.5%:1, the amount of lubricant lithium stearate added is 0.05% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.588μm is obtained.

[0071] Example 8

[0072] Triethyl acetyl citrate, PVDF and bismuth titanate are mixed in a weight ratio of 75%:5%:20% to obtain a premixed solution, and then the premixed solution is mixed with the ternary positive electrode material. The mixing process includes first stirring the mixed slurry under ultrasonic conditions for 1 hour, then standing it for 8 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.65 Co 0.07 Mn 0.28 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 1:1, the main component of the plasma activation gas is argon, which contains 10% volume of carbon dioxide, and the flow rate of the plasma activation gas is 50mL / min, and the power density is 0.05W / cm 2.

[0073] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 120°C and the drying time was 5 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 45%, the sintering temperature was 780°C and the sintering time was 5 hours to obtain a first coated mixed material.

[0074] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 0.5%:1, the amount of lubricant lithium stearate added is 0.05% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.553 μm is obtained.

[0075] Example 9

[0076] The premixed solution is obtained by mixing acetyl citrate n-butyl ester, PVDF and bismuth titanate in a weight ratio of 75%:5%:20%, and then the premixed solution is mixed with the ternary positive electrode material. The mixing process includes first stirring the mixed slurry under ultrasonic conditions for 1 hour, then standing and aging it for 8 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.65 Co 0.07 Mn 0.28 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 1:1, the main component of the plasma activation gas is argon, which contains 10% volume of carbon dioxide, and the flow rate of the plasma activation gas is 50mL / min, and the power density is 0.05W / cm 2 .

[0077] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 120°C and the drying time was 5 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 45%, the sintering temperature was 780°C and the sintering time was 5 hours to obtain a first coated mixed material.

[0078] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 0.5%:1, the amount of lubricant lithium stearate added is 0.05% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.378 μm is obtained.

[0079] Example 10

[0080] The premixed solution is obtained by mixing acetylcitrate tri(2-ethyl)hexyl ester, PVDF and bismuth titanate in a weight ratio of 75%:5%:20%, and then the premixed solution is mixed with the ternary cathode material. The mixing process includes stirring the mixed slurry under ultrasonic conditions for 1 hour, then standing it for 8 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operation is completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.65 Co 0.07 Mn 0.28 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 1:1, the main component of the plasma activation gas is argon, which contains 10% volume of carbon dioxide, and the flow rate of the plasma activation gas is 50mL / min, and the power density is 0.05W / cm 2 .

[0081] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 120°C and the drying time was 5 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 45%, the sintering temperature was 780°C and the sintering time was 5 hours to obtain a first coated mixed material.

[0082] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 0.5%:1, the amount of lubricant lithium stearate added is 0.05% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.445 μm is obtained.

[0083] Embodiment 11

[0084] The premixed solution is obtained by mixing triacetin, PVDF and bismuth titanate in a weight ratio of 75%:5%:20%, and then the premixed solution is mixed with the ternary cathode material. The mixing process includes stirring the mixed slurry under ultrasonic conditions for 1 hour, then standing it for 8 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.65 Co 0.07 Mn 0.28O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 1:1, the main component of the plasma activation gas is argon, which contains 10% volume of carbon dioxide, and the flow rate of the plasma activation gas is 50mL / min, and the power density is 0.05W / cm 2 .

[0085] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 120°C and the drying time was 5 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 45%, the sintering temperature was 780°C and the sintering time was 5 hours to obtain a first coated mixed material.

[0086] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 0.5%:1, the amount of lubricant lithium stearate added is 0.05% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.532 μm is obtained.

[0087] Example 12

[0088] Diethylene glycol ethyl ether acetate, PVDF and bismuth titanate are mixed in a weight ratio of 75%:5%:20% to obtain a premixed solution, and then the obtained premixed solution is mixed with the ternary positive electrode material. The mixing process includes first stirring the mixed slurry under ultrasonic conditions for 1 hour, then standing it for 8 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.65 Co 0.07 Mn 0.28 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 1:1, the main component of the plasma activation gas is argon, which contains 10% volume of carbon dioxide, and the flow rate of the plasma activation gas is 50mL / min, and the power density is 0.05W / cm 2 .

[0089] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 120°C and the drying time was 5 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 45%, the sintering temperature was 780°C and the sintering time was 5 hours to obtain a first coated mixed material.

[0090] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 0.5%:1, the amount of lubricant lithium stearate added is 0.05% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.387 μm is obtained.

[0091] Example 13

[0092] The difference from Example 1 is that the ratio of the acid ester solvent, the first additive and polyvinylidene fluoride during the first coating is 68%:30%:2%, and the weight ratio of the ternary positive electrode material to the premixed solution is 0.8:1. During the second coating, the weight ratio of the mixed material and the second additive is 1:10%, and the amount of lubricant added is 1% of the sum of the weight of the mixed material and the second additive.

[0093] The premixed solution is obtained by mixing triethyl citrate, PVDF and bismuth titanate in a weight ratio of 68%:30%:2%, and then the premixed solution is mixed with the ternary cathode material. The mixing process includes stirring the mixed slurry under ultrasonic conditions for 1 hour, then standing it for 8 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.65 Co 0.07 Mn 0.28 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 0.8:1, the main component of the plasma activation gas is argon, which contains 10% volume of carbon dioxide, and the flow rate of the plasma activation gas is 50mL / min, and the power density is 0.05W / cm 2 .

[0094] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 120°C and the drying time was 5 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 45%, the sintering temperature was 780°C and the sintering time was 5 hours to obtain a first coated mixed material.

[0095] The mixed material after the first coating, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 1:10%, the amount of lubricant lithium stearate added is 1% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above-mentioned mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.837 μm is obtained.

[0096] Comparative Example 1

[0097] The ternary material and bismuth titanate are mixed in a weight ratio of 80%:20% and dried under nitrogen circulation conditions. The molecular formula of the ternary material is LiNi 0.65 Co 0.07 Mn 0.28 O2, the drying temperature is 120°C, and the drying time is 5h; the dried mixture is then sintered in a compressed air atmosphere with a humidity of 45%, the sintering temperature is 780°C, and the sintering time is 5h to obtain the first coated mixed material.

[0098] The mixed material after the first coating obtained above, the second additive polythiophene and the lubricant lithium stearate are mixed, and then ball-milled for the second coating, wherein the weight ratio of the mixed material to the second additive is 0.5%:1, the amount of lubricant lithium stearate added is 0.05% of the sum of the weight of the mixed material and the second additive, the ratio of the weight of the grinding balls added during ball milling to the weight of the above mixture is 1:1, and after ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.317 μm is obtained.

[0099] Comparative Example 2

[0100] The premixed solution is obtained by mixing triethyl citrate, PVDF and bismuth titanate in a weight ratio of 75% 5%: 20%, and then the premixed solution is mixed with the ternary positive electrode material. The mixing process includes stirring the mixed slurry under ultrasonic conditions for 1 hour, then standing it for 8 hours, and continuously introducing plasma activation gas during the ultrasonic stirring and aging process. After the above operations are completed, a mixed slurry is obtained. Among them, the molecular formula of the ternary material is LiNi 0.65 Co 0.07 Mn 0.28 O2, the weight ratio of the added amount of the ternary cathode material to the premixed solution is 1:1, the main component of the plasma activation gas is argon, which contains 10% volume of carbon dioxide, and the flow rate of the plasma activation gas is 50mL / min, and the power density is 0.05W / cm 2 .

[0101] The mixed slurry obtained above was dried under nitrogen circulation conditions, wherein the drying temperature was 120°C and the drying time was 5 hours; the dried mixture was then sintered in a compressed air atmosphere with a humidity of 45%, the sintering temperature was 780°C and the sintering time was 5 hours to obtain a mixed material. The coated mixed material obtained above was ball milled, and the weight ratio of the grinding balls added during ball milling to the weight of the mixture was 1:1. After ball milling for 8 hours, a modified ternary positive electrode material with a particle size D50 of 3.273μm was obtained.

[0102] The contents of alkaline substances LiOH and Li2CO3 in the modified ternary positive electrode materials in the above-mentioned Examples 1 to 13 and Comparative Examples 1 to 2 before and after modification were tested, and related properties such as the specific surface area (BET) and powder compaction density of the materials were tested. The test results are shown in Table 2 below.

[0103] Among them, regarding the test method for the alkali content in the modified ternary positive electrode material before and after modification: weigh the test material according to the parameters shown in Table 1, accurate to 0.0001g, place the weighed sample in a 100mL beaker, add 50mL of deionized water, put the magnetic beads in the beaker and seal it with plastic wrap, then place the beaker on a magnetic stirrer and stir for about 15 minutes and then remove it; let it stand for 5 minutes, filter it with a glass funnel, and the filtered clear liquid is the solution to be tested.

[0104] Table 1

[0105]

[0106] Accurately transfer the solution to be tested into a 100mL beaker, place a stirring rotor, control the sample volume to about 50mL (make up with water if less than 50mL), place the beaker on the magnetic stirrer of the automatic potentiometric titrator, add 2 drops of phenolphthalein, select the HCl standard solution according to Table 1 and titrate it from red to colorless. The instrument will record the volume Ep1 (V1) of the HCl standard solution consumed at the chemical stoichiometric point and the pH; then add 2 drops of methyl orange and continue to titrate it from yellow to orange. The instrument will record the volume Ep2 (V2) of the HCl standard solution consumed at the chemical stoichiometric point and the pH. The analysis results of the alkali content in the sample are calculated in the following ways:

[0107] (1) When 2V1>V2, it contains LiOH and Li2CO3, and the calculation formula is as follows:

[0108]

[0109] (2) When 2V1<V2, it contains Li2CO3 and LiHCO3, and the calculation formula is as follows:

[0110]

[0111] (3) When 2V1 = V2, it contains only Li2CO3, and the calculation formula is as follows:

[0112]

[0113] Wherein, in the above calculation formula: c is the concentration of HCl standard solution (mol / L); V1(Ep1) is the volume of HCl standard solution consumed at the first equivalence point (mL); V2(Ep2) is the volume of HCl standard solution consumed at the second equivalence point (including the first equivalence point) (mL); V' is the volume of the sample solution (mL); V is the volume of the sample (mL); 23.95 is the molar mass of LiOH (g / mol); 73.89 is the molar mass of Li2CO3 g / mol; 67.96 is the molar mass of LiHCO3 g / mol; m is the mass of the sample (g).

[0114] Table 2

[0115]

[0116] The ternary positive electrode materials before and after modification in the above-mentioned Examples 1 to 13 and Comparative Examples 1 to 2 were respectively prepared into positive electrode sheets and button batteries according to the methods described below. The mixed slurry in the process of preparing the positive electrode sheets and the related performances of the positive electrode sheets and button batteries were tested. The test methods and the results obtained are shown in the following table.

[0117] Preparation of button cells:

[0118] The electrode active material (ternary positive electrode material before modification or modified ternary positive electrode material), conductive agent acetylene black and binder PVDF are mixed in a weight ratio of 90:5:5 to prepare a positive electrode slurry, wherein the preparation method includes: weighing the positive electrode material and acetylene black to an accuracy of 0.0001g, and mixing and grinding in a mortar for 30min. PVDF is dissolved in N-methylpyrrolidone to obtain a PVDF solution with a solute mass fraction of 2.5%, and the corresponding amount of solution is measured and slowly added to the mortar, mixed and ground until a uniform positive electrode slurry is formed. Cut out an aluminum foil of a suitable area and lay it flat on a smooth glass plate, and evenly apply the above-obtained slurry on the aluminum foil with a scraper, and completely volatilize and remove the organic solvent (NMP) therein at 100°C, and roll the pole piece with a roller press to control the compaction density of the pole piece at 3.0g / cc. A manual tablet press is used to cut the aluminum foil, and the area on the aluminum foil with the active material evenly coated is cut into positive electrode sheets with a diameter of 12 mm. The sheets are placed in a vacuum drying oven and dried at 100°C for 5 hours to remove the moisture in the positive electrode sheets. The sheets are then placed in a vacuum drying oven and dried at 100°C for another 5 hours to obtain positive electrode sheets that can be directly assembled into batteries.

[0119] The positive electrode sheet prepared as above is assembled into a button-type battery of model CR2016 to assemble a battery with lithium as the counter electrode that can be used for various electrochemical performance tests. The specific steps are: quickly transfer the positive electrode sheet to a glove box, take the positive electrode shell, place the positive electrode sheet with the active material facing up in the middle of the positive electrode shell, add electrolyte, place the diaphragm, add electrolyte, place the lithium sheet and nickel foam in sequence, and finally cover the negative electrode shell, place the battery on a button battery sealing machine, manually pressurize it to a certain pressure, and press and package it to obtain a button battery.

[0120] Button cell performance test: The test uses a LAND battery test system with model CT2001A. The program setting is first set to let the battery stand for 6 hours, wait for the electrolyte to fully infiltrate, and then start the electrochemical performance test. Since increasing the cut-off voltage can increase the discharge capacity of the material, the cycle stability of the material is tested at a high voltage of 4.5V in this application. In the rate performance test at room temperature 25℃, the rates are set to 0.2C, 0.33C, 1C, and 3C, and the charge and discharge voltage range is 2.8V to 4.5V. Set the charge and discharge rate to 1C, the charge and discharge voltage range to 2.8V to 4.5V, cycle 50 weeks, and test the capacity retention rate of the battery.

[0121] Button cell DCR growth rate test:

[0122] DCR test: The test is conducted by discharging for 30 seconds at a rate of 1C in a constant temperature box at 25°C. The calculation formula of DC discharge resistance (DCR) is as follows: DCR = (U0-U1) / I; U0 represents the voltage before discharging for 30 seconds, U1 represents the voltage after discharging for 30 seconds, and I represents the current at a rate of 1C. The button cell to be tested is placed in a constant temperature box at 25°C with a voltage range of 2.8V-4.5V and 0.2C charge and discharge cycles for two cycles. The average value of the discharge capacity of two cycles at 0.2C is defined as 100% state of charge (SOC), and then the capacity is discharged to 1 / 2 at a rate of 0.2C, which is defined as 50% SOC. The DCR of 50% SOC before the test is placed at high temperature is recorded as DCR0. The button cell is charged to 4.5V at a constant current and constant voltage rate of 0.2C in a constant temperature box at 25°C, i.e. 100% SOC state. Then place the button battery in a 90℃ constant temperature and humidity chamber for 24 hours. Then place the button battery in a 25℃ constant temperature chamber for 1 hour, repeat the 100% SOC constant volume and adjust to 50% SOC at 0.2C after shelving, and finally perform a DCR test at 50% SOC after shelving, and record it as DCR 50 . Growth rate before and after high temperature storage R% = (DCR 后 -DCR 前 ) / DCR 前 ×100, where DCR 前It means the DC internal resistance of 50% SOC at 1C rate tested at 25℃ before high temperature storage, and the DC internal resistance of 50% SOC at 1C rate tested at 25℃ after 90℃ high temperature storage is DCR 后 .

[0123] Slurry stability test during electrode preparation:

[0124] (1) The ternary positive electrode materials before and after modification in Example 1 were used to prepare positive electrode slurry, and 50 mL was taken and allowed to stand. During this period, the viscosity of the slurry at 0 h (i.e. before standing and after mixing), 2 h, 4 h, 8 h, 16 h, 32 h, and 64 h was tested. The obtained data were recorded and plotted. The results are as follows: Figure 3 As shown in the figure, the stability of the slurry can be reflected according to the fluctuation of the slurry viscosity within 64 hours.

[0125] (2) Regarding viscosity difference: The ternary positive electrode materials before and after modification of Examples 1 to 13 and Comparative Examples 1 and 2 were used to prepare positive electrode slurries. 50 mL of the positive electrode slurry was allowed to stand for 64 h. The viscosity of the slurry after mixing was tested first, and then the viscosity of the slurry after standing for 64 h was tested. The viscosity difference before and after standing was taken to reflect the stability of the corresponding slurry. The slurry viscosity difference was recorded as shown in Table 3.

[0126] (3) About fineness test: The fineness of the slurry can reflect the distribution of particles in the slurry. It can be combined with viscosity and other characteristics to comprehensively judge the stability of the slurry. Slurry with good dispersion has a more uniform particle distribution and is not easy to agglomerate and precipitate when left alone. The smaller the fineness, the better the stability of the slurry. The fineness test is carried out using the scraper fineness meter method.

[0127] (4) Regarding the difference in solid content: 50 mL of the positive electrode slurry prepared from the ternary positive electrode materials of Examples 1 to 13 and Comparative Examples 1 and 2 before and after modification were taken and allowed to stand for 64 h, and then the upper and lower layers of the slurry were taken. The solid content of the upper and lower layers of the slurry was tested respectively. The difference in solid content between the upper and lower layers can further reflect the sedimentation performance of the slurry, that is, the stability performance.

[0128] Pole piece rebound rate test: Pole piece rebound rate can be used to evaluate the processing performance of materials. The smaller the pole piece rebound rate, the better the processing performance of the corresponding material. The pole piece rebound rate calculation formula is: (pole piece thickness after rebound - pole piece thickness before rebound) / pole piece thickness before rebound × 100%, where the pole piece thickness before rebound is the thickness measured after the pole piece is manufactured, and the pole piece thickness after rebound is the thickness measured after the pole piece is placed at room temperature and under high-purity argon protection for 48 hours.

[0129] The modified ternary positive electrode materials in the above-mentioned Examples 1 to 13 and Comparative Examples 1 to 2 are prepared into positive electrode sheets and button batteries according to the above-mentioned methods before and after modification, respectively. The results of testing the positive electrode slurry in the process of preparing the positive electrode sheet and the related properties of the positive electrode sheet are shown in Table 3.

[0130] Table 3

[0131]

[0132]

[0133] The modified ternary positive electrode materials in the above-mentioned Examples 1 to 13 and Comparative Examples 1 to 2 before and after modification were respectively prepared into button batteries according to the above-mentioned method, and the battery charging and discharging performance and DC resistance growth rate and other related properties were tested. The results are shown in Table 4.

[0134] Table 4

[0135]

[0136]

[0137] As can be seen from Table 2, in Examples 1 to 12 of the present invention, the preparation method of the present invention is used to prepare the modified ternary positive electrode material, and the preparation conditions are controlled within the preferred range. The prepared modified ternary positive electrode material can significantly reduce the content of LiOH and Li2CO3 in the ternary positive electrode material before modification, effectively achieving the purpose of reducing the content of alkaline substances in the ternary material; in addition, the specific surface area characteristics and powder compaction density characteristics of the modified ternary positive electrode material compared to the ternary positive electrode material before modification are also significantly improved. Example 13 uses the preparation method of the present invention when preparing the modified ternary positive electrode material, but does not control the preparation conditions within the preferred range. The obtained modified ternary positive electrode material is also improved to a certain extent compared to the alkali content, specific surface area characteristics and powder compaction density characteristics before modification. Comparative Examples 1 to Comparative Examples 2 do not use the modification method of the present invention, and the degree of improvement of the obtained modified ternary positive electrode material compared to the alkali content, specific surface area characteristics and powder compaction density characteristics before modification is not ideal.

[0138] The data in Table 3 are the results of relevant performance tests of the ternary positive electrode materials before modification and the modified ternary positive electrode materials in Examples 1 to 13 and Comparative Examples 1 to 2 when they are prepared into positive electrode sheets. According to the above data analysis, it can be seen that when preparing the modified ternary positive electrode materials, the preparation method of the present invention is used and the preparation conditions are controlled within the preferred range, the prepared modified ternary positive electrode materials can be further improved in fineness, viscosity, resistivity and thickness rebound rate of the electrode sheet compared with the materials before modification. The changes in fineness and viscosity indicate that when the modified ternary positive electrode materials are used to prepare positive electrode sheets, the overall stability of the slurry is significantly improved; the resistivity of the modified ternary positive electrode materials is also significantly reduced, and the conductive properties are improved. Example 13 When preparing the modified ternary positive electrode materials, the preparation method of the present invention is used, but the preparation conditions are not controlled within the preferred range. The prepared modified ternary positive electrode materials have a slightly worse modification effect than Examples 1 to 12, but the relevant performance is also improved to a certain extent. However, Comparative Examples 1 and 2 did not adopt the modification method described in the present invention, and the effect of the modified ternary positive electrode material obtained was far different from the modification effect of the modified ternary positive electrode material prepared by the preparation method described in the present invention.

[0139] The data in Table 4 are the results of relevant performance tests of the ternary positive electrode materials before modification and the modified ternary positive electrode materials in Examples 1 to 13 and Comparative Examples 1 to 2 when prepared into batteries. It can be seen from Table 4 that when the modified ternary positive electrode materials prepared in Examples 1 to 12 are applied to batteries, the performance of various aspects such as battery capacity, capacity retention rate and DCR growth rate are better than the performance of the ternary positive electrode materials before modification when prepared into batteries. The modified ternary positive electrode material prepared in Example 13 is slightly worse than that in Examples 1 to 12 when applied to batteries, but it can still serve the purpose of further improvement. The performance of the modified ternary positive electrode materials prepared into batteries in Comparative Examples 1 to 2 is not significantly different from the effect before modification, and is very different from the effect shown in Examples 1 to 13.

[0140] In summary, the modified ternary positive electrode material prepared by the preparation method of the modified ternary positive electrode material of the present invention can significantly reduce the content of alkaline substances in the material, improve the compaction density and specific surface area of ​​the material and other properties; when it is used to prepare the positive electrode plate of the battery, the stability of the slurry is significantly improved, and the resistivity and the thickness rebound rate of the plate can also be further improved; and when the modified ternary positive electrode material of the present invention is applied to the battery, the battery capacity, capacity retention rate and DCR growth rate and other aspects of the performance of the battery are further improved. It can be seen that the method of the present invention has obvious progressive significance.

[0141] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified ternary positive electrode material, characterized in that: The preparation method comprises the following steps: Step (1), mixing an acid ester solvent, a first additive and polyvinylidene fluoride to obtain a premixed solution; the first additive is a salt of at least one of the metal elements Sn, Zn, Ti, Bi, Ta, Li and Zr; Step (2), mixing the premixed solution and the ternary positive electrode material to obtain a mixed slurry; Step (3), drying and sintering the mixed slurry to perform a first coating to obtain a mixed material; Step (4), mixing the mixed material, the second additive and the lubricant, and then ball milling for a second coating to obtain the modified ternary positive electrode material; the second additive is a conductive polymer additive.

2. The method for preparing the modified ternary cathode material according to claim 1, characterized in that: In terms of weight percentage, the first additive in the premixed solution is 5-20%, the polyvinylidene fluoride is 5-20%, and the balance is the acid ester solvent; Preferably, the weight ratio of the ternary positive electrode material to the premixed solution is (1-5):

1.

3. The method for preparing the modified ternary cathode material according to claim 1, characterized in that: The weight ratio of the mixed material to the second additive is 1:(0.01% to 1%); the added amount of the lubricant is 0.01% to 0.1% of the sum of the weight of the mixed material and the second additive.

4. The method for preparing the modified ternary cathode material according to any one of claims 1 to 3, characterized in that: The acid ester solvent is one or more of tributyl citrate, triethyl citrate, tri-n-hexyl citrate, tri(2-ethyl)hexyl citrate, acetyl tributyl citrate, acetyl triethyl citrate, acetyl n-butyl citrate, acetyl tri(2-ethyl)hexyl citrate, triacetin and diethylene glycol ethyl ether acetate; Preferably, the first additive is one or more of zinc stannate, bismuth titanate, lithium tantalate, barium titanate, zirconate titanate; Preferably, the second additive is polythiophene and / or sulfonated lignin; Preferably, the lubricant is lithium stearate and / or zinc stearate.

5. The method for preparing the modified ternary cathode material according to any one of claims 1 to 3, characterized in that: The mixing process in step (2) comprises: subjecting the premixed solution and the ternary cathode material to ultrasonic treatment, followed by aging, and introducing plasma activated gas during the ultrasonic and aging processes; Preferably, the plasma activation gas is an inert gas containing 5-20% carbon dioxide, and preferably the inert gas is at least one of argon and helium; Preferably, the amount of the plasma activated gas introduced is 20 to 100 mL / min; Preferably, the power density of the plasma activated gas is 0.01 to 5 W / cm 2 ; Preferably, the ultrasonication time is 0.5 to 5 hours; preferably, the aging time is 1 to 12 hours.

6. The method for preparing the modified ternary cathode material according to any one of claims 1 to 4, characterized in that: The molecular formula of the ternary positive electrode material is LiNi x Co y M 1-x-y O2, wherein 0.5≤x<1, 0<y≤0.1, and (x+y)<1, and M is Mn and / or Al.

7. The method for preparing the modified ternary cathode material according to any one of claims 1 to 4, characterized in that: The sintering in step (3) is carried out in a compressed air atmosphere with a humidity of 40 to 70%; Preferably, the sintering temperature is 700-900°C; Preferably, the sintering time is 2 to 8 hours; Preferably, the drying is carried out under nitrogen circulation conditions, the drying temperature is 100-200° C., and the drying time is 5-25 hours.

8. The method for preparing the modified ternary cathode material according to any one of claims 1 to 4, characterized in that: During the ball milling, grinding balls are added to the mixture of the mixed material, the second additive and the lubricant; Preferably, the weight ratio of the grinding ball to the mixture consisting of the mixed material, the second additive and the lubricant is 1:(1-5); Preferably, the ball milling time is 4 to 12 hours; Preferably, the particle size of the ternary positive electrode material after ball milling is 2.5≤D50≤4μm.

9. A modified ternary cathode material, characterized in that: Prepared according to the preparation method described in any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: It includes a battery positive electrode prepared from the modified ternary positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Preparation method of improved lithium ion battery positive electrode material

    CN105355842A

  • PVDF-coated lithium-ion battery separator and preparation method thereof

    CN105552277A

  • Positive electrode sheet and lithium ion secondary battery with same

    CN108539122A

  • Two-layer coated modified ternary cathode high-nickel material and preparation method thereof

    CN109830651A

  • Modified high-nickel ternary positive electrode material and preparation method thereof

    CN112864369A